2016
DOI: 10.18632/oncotarget.8215
|View full text |Cite
|
Sign up to set email alerts
|

Tall cell variant of papillary thyroid carcinoma: current evidence on clinicopathologic features and molecular biology

Abstract: Tall cell variant (TCV) of papillary thyroid carcinoma (PTC) has been recognized for the past few decades as an entity showing aggressive biological behavior; however, there is considerable controversy regarding the definition, clinical and pathological features of TCV because of its rarity and difficult diagnosis. No clinical features can accurately diagnose TCV. Thus, the results of histocytology, immunohistochemistry and molecular genetics tests have important clinical implications for diagnosis. Given the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 63 publications
7
55
0
5
Order By: Relevance
“…Although there is a lack of consensus on whether the TCV of PTC is varied from the classical PTC in terms of tumor size at presentation (10), a previous review revealed that the mean tumor diameter in all cases of the TCV of PTC was 20 mm, by comparison with 19 mm in classical PTC (10). The current series of the TCV of PTC was compared with the two CaFVs to determine if, irrespective of age and size, TCV is more aggressive than its classical and follicular counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a lack of consensus on whether the TCV of PTC is varied from the classical PTC in terms of tumor size at presentation (10), a previous review revealed that the mean tumor diameter in all cases of the TCV of PTC was 20 mm, by comparison with 19 mm in classical PTC (10). The current series of the TCV of PTC was compared with the two CaFVs to determine if, irrespective of age and size, TCV is more aggressive than its classical and follicular counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TCV exhibit poorer survival than those with classical PTC (5,10). The tall-cell feature alone remains a significant prognostic factor for disease-specific mortality when the major prognostic factors for thyroid cancer are controlled for, including age and extrathyroidal extension (11).…”
Section: Introductionmentioning
confidence: 97%
“…PTC is derived from the follicular epithelium [3] and includes many histological variants such as tall cell, columnar cell, diffuse sclerosing, solid, and hobnail [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…It is composed predominantly of elongated (“tall”) tumor cells (height/width ≥3/1) with abundant dense oxyphilic granular cytoplasm and the typical nuclear changes of PTC . In contrast to conventional PTC, the TCV has a relatively higher prevalence in males and tends to occur in older patients . It often presents at advanced stages and has a higher incidence of local recurrence and distant metastasis .…”
Section: Tall Cell Variantmentioning
confidence: 98%